Prevalensi Dan Faktor Risiko Hipertensi Pada Sopir Truk Di Wilayah Pesisir Belawan Tahun 2026 - Kartika Sari Rizki; Tasya Eka Putri Tarigan; Riwana Br Manalu; Widya Yanti Sihotang (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Hypertension is a global health problem often referred to as the "silent killer" because it generally does not cause symptoms until serious complications occur. Truck drivers in the coastal area of Belawan are exposed to significant occupational risk factors, including prolonged sitting, long working hours, and low physical activity. Objective: To analyze the prevalence of hypertension and factors associated with hypertension among truck drivers in the Belawan coastal area in 2026. Methods: A quantitative study with observational analytic cross-sectional design involving 150 active truck drivers at Jl. Baru Logistic, Bagan Deli, Medan Belawan. Data were collected through structured interviews and blood pressure measurement using a calibrated Omron digital sphygmomanometer. Data were analyzed by univariate, bivariate (Chi-Square), and multivariate (multiple logistic regression) methods. Results: The prevalence of hypertension was 50% (75 of 150 respondents) and prehypertension was 30% (45 respondents of 150 respondents). Bivariate analysis showed significant associations between hypertension and length of service (p=0.001), working duration (p=0.002), and physical activity (p=0.007). night shift work (p=0.068) Lifestyle (p=0.989), stress level (p=0.337), and JKN ownership (p=0.337) were not significantly associated. Multivariate analysis indicated that length of service (OR=2.207; p=0.008) and working duration (OR=0.2166; p=0.003) were significantly associated with hypertension. Conclusion: Hypertension has a very high prevalence among truck drivers in the Belawan coastal area (50%) prehypertension was 30%, with length of as the main risk factors. Targeted health promotion and preventive interventions for this occupational group are urgently needed.